2009
DOI: 10.1097/nmd.0b013e3181c29a23
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Antibody Titers and History of Suicide Attempts in Patients With Recurrent Mood Disorders

Abstract: Toxoplasma gondii (T.gondii) is an obligate intracellular protozoan parasite infecting one-third of the world population, residing relatively silently in the brain of the immunocompetent host. We hypothesized that T.gondii seropositivity and serointensity are associated with having a history of attempting suicide and, in those attempting suicide, a greater number of attempts. T.gondii seropositivity and antibody titers were compared between (a) patients with recurrent mood disorders with history of suicide att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
172
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(191 citation statements)
references
References 29 publications
13
172
4
Order By: Relevance
“…Patients with recurrent mood disorders with history of suicide attempt had higher T. gondii antibody titers than patients with recurrent mood disorders without history of suicide attempt (Arling et al 2009). In a case-control study, the association between latent toxoplasmosis and cognitive performance with a battery of standardized, widely employed neuropsychological tests were assessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with recurrent mood disorders with history of suicide attempt had higher T. gondii antibody titers than patients with recurrent mood disorders without history of suicide attempt (Arling et al 2009). In a case-control study, the association between latent toxoplasmosis and cognitive performance with a battery of standardized, widely employed neuropsychological tests were assessed.…”
Section: Discussionmentioning
confidence: 99%
“…gondii can alter brain function and induce changes in the behavior of its intermediate hosts (Mortensen et al 2007;Kar and Misra 2004;Arling et al 2009). In male LongEvans rats, Latent Toxoplasma infection resulted to reduced the normal aversion to cat odor and converted it into a mild attraction (Vyas et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In addition, T. gondii infection has been repeatedly found to be associated with mental illnesses, including schizophrenia, self-harm, and bipolar depression, although the evidence is not yet sufficient to imply a causal relationship. [4][5][6][7][8] Periodically, the Centers for Disease Control and Prevention (CDC) tests serum samples from the National Health and Nutrition Examination Survey (NHANES) for T. gondii antibodies to estimate the prevalence of T. gondii infection in the United States. Once infected, people generally retain a chronic infection, particularly in the cells of the muscles and brain.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic T. gondii infection in the human population has been correlated with a diverse range of human diseases, including Alzheimer's and Huntington's [12,13]. The association between T. gondii infection and mental health disorders such as depression, psychosis, self-directed violence and schizophrenia have been widely studied [14][15][16][17][18]. Schizophrenia is the most extensively investigated of these; indeed two meta-analyses of the association collectively spanning 70 studies over 55 years concluded that there is a positive correlation between T. gondii seropositivity and schizophrenia [19,20].…”
Section: Host Behavioral Consequencesmentioning
confidence: 99%